2007
DOI: 10.1007/s00276-007-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Position of the mental foramen in a northern regional Jordanian population

Abstract: The position of the mental foramen on panoramic radiographs in this selected group of Jordanians is most commonly below and between the mandibular premolar teeth, and the most frequent appearance was the continuous type. These results are similar to previous findings in Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
80
13
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 26 publications
27
80
13
4
Order By: Relevance
“…51.5% of the in the Indian population is between the second premolar and the first molar, though 45.5% lies along the long axis of the second premolar. Al-Khateeb found, with advancing age, that there was an increase in the frequency of more posterior positioning of the mental foramen; 15 this trend was seen in the present study though modal positions did not change with age except that in the >27-year-old Indian population it was in line with the long axis of the second premolar, with an additional 47% between the second premolar and first molar.…”
Section: Discussionsupporting
confidence: 62%
“…51.5% of the in the Indian population is between the second premolar and the first molar, though 45.5% lies along the long axis of the second premolar. Al-Khateeb found, with advancing age, that there was an increase in the frequency of more posterior positioning of the mental foramen; 15 this trend was seen in the present study though modal positions did not change with age except that in the >27-year-old Indian population it was in line with the long axis of the second premolar, with an additional 47% between the second premolar and first molar.…”
Section: Discussionsupporting
confidence: 62%
“…1 Among Jordanians, Al-Khateeb, Al-Hadi Hamasha and Taha Ababneh studied panoramic radiographs and found that the most common position for the mental foramen was lower and between the mandibular premolar teeth (1st and 2nd lower premolars). 2 However, this result was consistent with others among Caucasian population studied by Neiva, Gapski and Lay Wang. Among Thais, Apinhasmit, Chompoopong and Methathrathip found a mean measurement of 28.52 卤 2.15 mm between symphysis and mental foramen, and also found that the mental foramen was commonly situated in line with the second lower premolar.…”
Section: Introductionsupporting
confidence: 82%
“…However, individual variation could lead to other locations ranging from above to below the level of apices of mandibular premolars (Al-Khateeb et al, 2007). Additionally, the mental foramen on panoramic radiographs in relation to the mental canal commonly provides continuous appearance.…”
Section: Introductionmentioning
confidence: 99%